HOW TO WIN INDONESIAN MOVIE VIEWERS: CASE OF VILLAGE CINEMA AUSTRALIA - Slamet Wahyudi (Jurnal Bisnis Terapan, 2018)
Australia and Indonesia have a close relationship in many busineses areas including entertainment. This paper focuses on how Australia’s Giant Cinema expands its business into Indonesia. Since many Indonesians stayed in Australia and experience directly Australian products and services, they are aware that Australian products had a high quality. Fortunately, vice versa, Australians are quite familiar with Indonesian culture. This is an opportunity for Village Cinema to enter Indonesian Market. This paper will start with market segmentation and Village cinema’s target customers; furthermore it draws Village’s position map comparing to its competitors in Indonesian market. Not to mention that Indonesian Cineplex has been quite established in many Indonesian primary cities with XX1, 21 Cineplex and CGV formerly Blitz Megaplex lead the market share accordingly. However, there were some marketing strategies Village Cinema should choose, including product, price, promotion and distribution strategy. There is a chance for Village cinemas to be a multinational cinema company player in Indonesia.